Hierarchical genetic interactions between FOXG1 and LHX2 regulate the formation of the cortical hem in the developing telencephalon - Godbole, Geeta (Development, 2018)
During forebrain development, a telencephalic organizer called the cortical hem is crucial for inducing hippocampal fate in adjacent cortical neuroepithelium. How the hem is restricted to its medial position is therefore a fundamental patterning issue. Here, we demonstrate that Foxg1-Lhx2 interactions are crucial for the formation of the hem. Loss of either gene causes a region of the cortical neuroepithelium to transform into hem. We show that FOXG1 regulates Lhx2 expression in the cortical primordium. In the absence of Foxg1, the presence of Lhx2 is sufficient to suppress hem fate, and hippocampal markers appear selectively in Lhx2-expressing regions. FOXG1 also restricts the temporal window in which loss of Lhx2 results in a transformation of cortical primordium into hem. Therefore, Foxg1 and Lhx2 form a genetic hierarchy in the spatiotemporal regulation of cortical hem specification and positioning, and together ensure the normal development of this hippocampal organizer.